دراسة تصنيفية مقارنة لثلاثة أنواع من جنس Simocephalus Schoedler,1858 رتبة القشريات متفرعات القرون( Cladocera- Daphniidae)، اثنان منها يسجلان للمرة الأولى - زيني, أديب (Latakia University Journal -Biological Sciences Series, 2019)
جمعت عينات العوالق الحيوانية من الأوساط المائية العذبة من الخزان المائي لسد الصوراني (طرطوس)، من المنطقة الشاطئية والغنية بالنباتات خلال صيف 2008-2009 م، إضافة إلى العينات المجموعة سابقاً من منطقة الهنادي من البرك الترابية المؤقتة والمحفوظة بالفورمالين منذ عام 1999م . تم من خلال دراسة العينات تسجيل نوعين جديدين تابعين للجنس: Simocephalus وهما S.expinosus و S.serrulatus ، إضافة إلى النوع S.vetulus المسجل سابقاً. تنتمي إلى فصيلة الـ. Daphniidae تم إجراء دراسة تصنيفية مقارنة لأهم الصفات التصنيفية الشكلية للأنواع الثلاثة مع تبيان توزعها الجغرافي. The specimens of freshwater zooplankton have been collected from a reservoir (AL-SUORANI –TARTUS) from the littoral zone among the vegetations, in addition to specimens collected previously from freshwater temporary ponds ( AL-HANADI- LATTAKIA) and preserved in Formalin since 1999. By treating the samples, two new species of Genus Simocephalus were recorded for the first time ( S.expinosus and S.serrulatus ), in addition to the species S.vetulus recorded previously. These species belong to the Family of Daphniidae. A comparative taxonomic study has also been conducted on the best morphological characteristics of the three species according to their geographical distribution.